Disseminação tecidual de toxoplasma gondii e resposta humoral após reinfecção experimental com cepas atípicas obtidas de casos congênitos de toxoplasmose humana em Minas Gerais - Gabriella de Lima Bessa (2017)
The paradigm that Toxoplasma gondii infection generate a sterilizing protective immune was broken by case studies in which reinfection was observed in immunocompetent pregnant women in chronic phase of toxoplasmosis. Since then, several murine models have been proven that immunoprotection against a previous T. gondii infection may be violated after reinfection with strains of different genotypes. The present study aimed to evaluate the events occurring after reinfection of mice by parasite strains of distinct genotypes, using bioassay, PCR and analysis of humoral immune response. Animals were first infected with the non-virulent TgCTBR5 strain and after 45 days these animals were challenged with the virulent TgCTBr9 or EGS strains, all of them isolated from human cases of congenital toxoplasmosis. The animals were sacrificed in the first hours after challenge (2, 4, 8, 12, 24 and 48 hours after challenge) and 7, 14 and 30 days after challenge. At these moments, bowel, mesenteric lymph nodes, lungs and brain were collected for bioassay analysis and to obtain DNA samples to PCR-RFLP. These two techniques were used to distinguish strains of T. gondii in possible process of reinfection. Blood samples were collected to measure the level of total IgG, IgG1, IgG2a, IgM and IgA by ELISA. Mortality and morbidity also were evaluated by survival curves and weight loss. The reinfected animals survived and presented reduced morbidity after challenge with the virulent strains. It was observed a fast and significant increase in levels of IgG1 anti-T. gondii at the 7th and 14th day after challenge, when compared to control group. In the other groups, there was no significant difference in the antibody levels after challenge. The dissemination of virulent strains in animals with previous chronic infection was different when compared to animals infected only with TgCTBr9 or EGS strains, with an early arrival of parasite in the gut, lung and brain (TgCTBr9 strain), and only in the lung (EGS strain) few hours after the challenge.